A sociological interpretation of the curriculum changes in the social studies program of the 2 - 2 plan - Garcia, Elsa R. 1937- (s.n.], 1963)
This is an analysis of the social bases of the curricular changes in the 2-2 plan, especially in the social studies subjects prescribed in our public secondary schools. These changes were analyzed from the sociological point of view, in the light of the social changes in Philippine Society, antecedent to, or contemporary to, the curriculum revision.